Anatomia e ultraestrutura de sítios de síntese de óleo essencial e cultivo de vitroplantas de Polygala paniculata L - Nery, Lays Araújo (2017)
Polygala paniculata is a medicinal species, whose root extract is used in the treatment of dislocations, trauma and ophidian accidents, therapeutic properties corroborated by science. The medicinal characteristic of plants is usually related to the presence of secretory structures specialized in the synthesis, accumulation and secretion of compounds with therapeutic activity. There are reports of trichomes, cavities and secretory cells of essential oils in P. paniculata. However, little is known about the development, chemical composition and secretory process of these structures. Species with medicinal value have been the target of different biotechnological techniques such as in vitro cultivation, with a view to maximizing the production of bioactive compounds. Species respond in different ways to the manipulation of in vitro conditions, such as light quality, gelling agents and sucrose concentration, which can result in changes in the quality of the plants and, consequently, the secretion produced. Thus, the present study aimed to (1) identify and analyze the development and secretory sites of essential oils; (2) to investigate the subcellular aspects and mechanisms of synthesis, accumulation and release of secretion; (3) Compare the ultrastructural aspects between the identified secretory sites and (4) to evaluate the effects of manipulation of in vitro conditions (light quality, gelling agents and sucrose concentration) on the leaf anatomy of P. paniculata. Polygala paniculata presents three secretory sites of essential oils: trichomes in leaves and stems, cavities in leaves and cortical cells in roots. The development of trichomes and cavities involves the process of programmed cell death. Trichomes, cavities and cortical root cells have the secretion composed of essential oils. The subcellular characteristics of the secretory structures studied are similar and are related to the chemical nature of the secretion. In the in vitro culture, the factors evaluated altered the leaf morphoanatomy of P. paniculata. Fluorescent lamp treatments induced the development of seedlings and the anatomical differentiation similar to that observed in ex situ plants. Treatments with sucrose concentration of 30 g L -1 in agar in 15 gL -1 in Phytagel induced increase in leaf thickness by increasing the cell volume of epidermal cells, lacunar parenchyma and reduction of intercellular spaces. The present study elucidated the structural and viiimechanism of the secretion of essential oils in P. paniculata. The effect of the in vitro conditions on the growth and foliar anatomy of the species can appreciate and subsist to improve in protocols of in vitro cultivation of the species.